the The Role of Family Planning Counselor in Preventing Families At Risk of Stunting (Case Study in Saragi Village, Pasarwajo District, Buton Regency) - Wa Ode Nurmin; Nastia Nastia; Herman Lawelai; Junaid Gazalin (Jurnal Ners, 2026)
Stunting is a chronic nutritional problem that has long-term impacts on children's physical growth, cognitive development, quality of life, and future productivity. Efforts to prevent stunting require multi-sectoral interventions, one of which is through optimizing the role of Family Planning (KB) counselors and Posyandu (Integrated Service Post) cadres as key actors at the community level. This study aims to analyze the role of KB counselors in preventing stunting in at-risk families in Saragi Village, Buton Regency, by reviewing the dimensions of education and counseling, family assistance, cross-sector coordination, and program monitoring. The research approach used a qualitative method with in-depth interviews with KB counselors, Posyandu cadres, pregnant women, families of toddlers, and community leaders. The results showed that KB counselors have a significant contribution in increasing family knowledge and awareness regarding the definition of stunting, its causative factors, and its impact on child health. Education was provided through group counseling, IEC, and home visits, which have proven effective in influencing nutritional behavior, parenting patterns, and utilization of health services. In terms of mentoring, extension workers conduct regular visits to monitor the condition of pregnant women and toddlers, detect stunting risks, and provide nutritional and health recommendations tailored to the family's circumstances. Coordination with health workers, village officials, and Posyandu (Integrated Service Post) cadres strengthens the program's effectiveness, although challenges remain, including limited facilities and cross-sectoral workloads. Furthermore, a family's economic situation significantly impacts the ability to provide nutritious food, so extension workers play a role in providing adaptive nutrition management strategies tailored to household capacity. This study concludes that the success of stunting prevention is influenced by the synergy between the active role of family planning extension workers, the support of Posyandu cadres, and the behavior and well-being of families.